Movies on TV and videocassette. - Scheuer, Steven H. (Toronto Bantam Books, 1989)
Annual.
Editor: Steven H. Scheuer.
Keywords: Television broadcasting of films -- Catalogs -- Periodicals; Motion pictures -- Catalogs -- Periodicals; Video recordings -- Catalogs -- Periodicals